Effect of the dietary fat sources on performance, liver fatty acid composition and meat cholesterol content in broiler - Khatun, Jannatara; Loh, Teck Chwen; Akit, Henny; Foo, Hooi Ling; Mohamad, Rosfarizan (Science Publishing Corporation, 2018)
A study was conducted to evaluate the effect of feeding diet containing palm oil (PO) and sunflower oil (SO) and their combination on bird performance, liver fatty acid profile and meat cholesterol content of broiler. A total of 144 day-old broiler chicks (Cobb) randomly assigned into four dietary treatments and fed for six weeks. The dietary treatments were T1, 6% PO (control); T2, 4% PO + 2% SO; T3, 2% PO + 4% SO; and T4, 6% SO. The body weight gain increased and feed conversion ratio (FCR) reduced with the increasing level of unsaturated fatty acid sources oil (SO) compared to control group (PO). Significantly higher (P<0.05) overall daily body weight gain and lower FCR were found in broilers fed dietary treatments T3 compared to other treatments. However, no differences (P<0.05) were found in daily body weight gain and FCR among the two combination of oil and SO alone. Dietary treatments influence the fatty acid composition of liver and increasing the dietary SO decreased the level of C16:0, C18:0, C18:1n-9, SFA and MUFA and increased the C18:2n-6, UFA: PUFA, UFA: SFA and PUFA: SFA. Birds fed PO had higher cholesterol concentration in meat which was decreased by supplementation of SO in broiler diet. However, cholesterol concentration was not differed in meat among the dietary SO and combination of SO and PO. It could be concluded that supplementation of a combination of PO and SO in broiler diet increased performance, altered the fatty acid composition of liver tissue and decreased cholesterol content of meat which may have a favorable impact on consumer’s health.